Photoinduced magnetic linear dichroism in a YIG:Co film - Miloslavska, O. V.; Kharchenko, Yu. N.; Kharchenko, N. F.; Yurko, V. G.; Stupakiewicz, A.; Maziewski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The spectra of linear dichroism induced by magnetic field are observed in a cobalt-doped yttrium iron garnet (YIG:Co) film grown in the (001) plane. The linear dichroism spectra are highly sensitive to the orientation of the magnetic field. The spectrum measured with the magnetic field directed along the crystallographic axis [100] turned out to have a form identical to the spectrum of the "rigid" photoinduced linear dichroism, known from earlier experiments. The similarity of these spectra may be regarded a sevidence of the magnetic origin of the major part of the optical anisotropy induced by light with polarization E | | [100] in the nonmagnetized YIG:Co film.